Sight Beyond Sight: A Conceptual Exploration of the 'Gaze' in Facilitating Simulations. (June 2021) - Naweed, Anjum; Leigh, Elyssebeth
Background: This article connects disparate components insimulation . The central component is that facilitators managesimulations as learning contexts. The second concerns a perception ofsimulations as safe containers, implying the existence of impermeable barriers betweensimulation and dangers of reality. However, when stepping into thefacilitation space, facilitators encounter a third component—the gaze . A concept from critical theory and psychoanalysis, this refers to acts of seeing and being seen, of/by themselves and others, and can engender heightened awareness as facilitators see themselves from the focal point of multiple lens, and within a container that may not be so impermeable. Aim: To increase understanding ofsimulation skills and development options for facilitators, we explore these components using: a)novice to expert progression ; b)power relationships ; and c) thebody memory as key factors which may influence the intensity and direction of awareness. Method: A narrative-based analysis of literature examines instances where awareness of self, and/or others influences how facilitators operate withinsimulations . Results: Aware thatsimulations create uncertainties, facilitators may experience greater anxiety than those managing non-facilitation settings. They must navigate participants through emergent conditions wherein the unexpected can conspire to render safe containers permeable, and alter participants' expectations. Increased understanding of the impact of gaze may enable facilitators to respond flexibly to unanticipated developments. Conclusions: Understanding the impacts of the gaze within and beyond asimulation may enable facilitators to prepare internally—and perform externally. A conceptual framework is developed to assist facilitators reflect and identify applications.